CONTESTING INFIDELITY AND RELIGIOUS AUTHORITY IN DIGITAL INDONESIA: The Discursive Contestation of the Hadith al-Ḥamw al-Mawt on Social Media - Zairina, Wardah; Zamzami, Mukhammad; Muktafi, Muktafi; Albaar, Abdullah; Hegazy, Wael (Journal of Contemporary Islam and Muslim Societies, 2025)
This study examines the discursive contestation surrounding the hadith al-Ḥamw al-Mawt (The in-law is Death) within Indonesian digital Islam. Drawing on Fairclough's Critical Discourse Analysis approach and Campbell's theory of Digital Religion, the study analyzes the Instagram-based da‘wah content produced by the account @ismaelkholilie as a site where religious meaning and authority are actively constructed and contested. It argues that the hadith is recontextualized from a classical moral injunction into a digital narrative addressing infidelity, family ethics, and mahram boundaries in contemporary Muslim households. The findings demonstrate that social media functions not merely as a medium of religious dissemination but as a discursive arena in religious authority negotiated and reconfigured through digital credibility, algorithmic visibility, and audience interactivity. By situating Indonesia as a critical site of digital religious practice, this article contributes to broader debates on religious authority and meaning-making in Digital Islam.Keywords: Digital hadith, infidelity, al-Ḥamw al-Mawt, religious authority, digital religion